DIALEKTIKA PERADABAN: KONTRIBUSI ISLAM DALAM PEMBENTUKAN TRADISI ILMIAH DUNIA BARAT - Dwi Rezky Wahyuni; Hasaruddin; Aksa; St. Nurlailah (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2026)
This article aims to critically reconstruct the contribution of Islamic civilization to the formation of the Western scientific tradition and to uncover the dynamics of the intercivilizational dialectics underlying it. This research uses a qualitative approach based on literature review, with a historical methodological framework encompassing heuristics, source criticism, interpretation, and historiography, to systematically trace and analyze the process of transmission and transformation of scientific knowledge. The results of the study indicate that institutions such as the Bayt al-Hikmah and the intellectual contributions of figures such as Ibn Sina, Al-Khwarizmi, and Ibn Rushd played a fundamental role in developing and transmitting the scientific tradition to the West, despite often being marginalized in Eurocentric historiography. Implicatively, this research emphasizes the urgency of reconstructing an integrative scientific paradigm through epistemological dialogue between Islam and the West to build a more holistic, inclusive, and civilized scientific system.